Bilayer Film Type of Unfolding Drug Delivery System for the Dual Release of Proton Pump Inhibitor and H2 Receptor Antagonist - Marina, Koland (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: This study was aimed at formulating and evaluating a bilayer unfolding film type drug delivery system for the dual release of proton pump inhibitor, rabeprazole sodium (RS) and H2 receptor antagonist, famotidine. Materials and Methods: Polymers such as polyvinyl alcohol hot, chitosan, and hydroxypropylmethyl cellulose E15 LV were used as film forming agents and glycerol as plasticizer. Enteric microspheres of RS were prepared by solvent evaporation and the films by solvent casting method. Microspheres were evaluated for production yield, entrapment efficiency, particle size, and in vitro drug release study. Optimized formulations of microspheres based on drug entrapment efficiency and in vitro drug release were incorporated into immediate release layer designed to disintegrate quickly. The individual layers, i.e., the immediate release layer containing RS microspheres and a gastro-retentive layer containing famotidine were subjected to various tests for uniformity of weight, thickness, folding endurance, uniformity of drug content, tensile strength, in vitro drug release, swelling index, and surface area. Results and Discussion: The immediate release layer disintegrated within 15 min while the gastro-retentive layer retained its integrity for more than 8 h. The evaluation of the assembled bilayer system of gastro-retentive layer and immediate release layer for in vitro drug release produced similar results as that for individual layers. In vivo X-ray radiography in rabbits confirmed the ability of the famotidine layer to be retained in the stomach for more than 8 h and the immediate release of the enteric RS microspheres for availability in the intestine. Conclusion: The bilayer unfolding film was successful in gastro retention and achieving the dual release of rabeprazole and famotidine and has the potential in the effective management of gastroesophageal reflux disease.